Woody and Herbaceous Plants of Inner Asia: Species Richness and Ecogeorgraphic Patterns - Sandanov, D. V.; Y. Liu; Wang, Zhiheng; Korolyuk, A. Yu (Contemporary Problems of Ecology, 2020)
The diversity of vascular plants in Inner Asia has been researched; the main environmental factors determining the distribution of species belonging to various life forms and having different distribution range sizes have been identified. The key factors determining species diversity in Inner Asia are past climate changes and precipitation parameters. By contrast, the temperature conditions of the current climate do not affect the species richness significantly. The following current climatic parameters are important for woody plants: precipitation seasonality, mean precipitation in winter and spring, and diurnal range of temperature. Quite the opposite, the species richness of herbaceous plants is determined by climate-change velocity from the mid-Holocene and Last Glacial Maximum, the spatial heterogeneity of precipitation, and mean summer temperatures. Over time, distribution ranges of rare plants in the studied region may be reduced due to the increasing aridization.